2022
DOI: 10.17925/ee.2022.18.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Tirzepatide: A Novel, Once-weekly Dual GIP and GLP-1 Receptor Agonist for the Treatment of Type 2 Diabetes

Abstract: Gastrointestinal hormones are currently used to treat type 2 diabetes mellitus (T2D). Incretin preparations with gastric inhibitory polypeptide (GIP) activity or glucagon-like peptide-1 (GLP-1) provide new means for controlling blood glucose levels, body weight, and lipid metabolism. GIP, an incretin, has not been used due to lack of promising action against diabetes. However, recent studies have shown that GIP has an important effect on glucagon and insulin secretion under normoglycaemic conditions. Co-existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
0
9
0
1
Order By: Relevance
“…The GLP-1 receptor agonists have a wide range of beneficial effects as well as therapeutic potential concerning the cardiovascular system, especially via their inhibition of the development, progression, and rupture of atherosclerotic plaques, as proven by multiple studies [ 34 , 35 ]. It has been proven that any long-acting glucagon-like peptide-1 receptor (GLP-1R) agonist has anti-inflammatory properties similar to those of natural GLP-1 and can therefore help to protect organs like the heart and kidneys [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The GLP-1 receptor agonists have a wide range of beneficial effects as well as therapeutic potential concerning the cardiovascular system, especially via their inhibition of the development, progression, and rupture of atherosclerotic plaques, as proven by multiple studies [ 34 , 35 ]. It has been proven that any long-acting glucagon-like peptide-1 receptor (GLP-1R) agonist has anti-inflammatory properties similar to those of natural GLP-1 and can therefore help to protect organs like the heart and kidneys [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, GIP is found to reduce oxidative stress in human endothelial cells and inflammatory cytokine release in visceral adipose tissue [ 34 ]. Pharmacological concentrations of GIP agonists are more likely to yield protective effects against atherosclerosis [ 36 ]. Nevertheless, further studies are required to obtain absolute clarity regarding the stimulation of GIP in the cardiovascular system [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…In 2022, the FDA approved the use of tirzepatide, a new medication that works as a dual GIP/GLP-1 receptor agonist (also known as "twincretin"), which causes a synergistic effect by enhancing the insulin response and producing a glucagonostatic effect during hyperglycemia [38]. Twincretins have similar effects to GLP-1RAs and, therefore, they also complete 6/8 pieces of the puzzle: the liver, muscle, pancreas (alpha and beta cells), gut, and brain.…”
Section: Antihyperglycemic Agents (Figure 2: Color-coded By Medication)mentioning
confidence: 99%
“…More research is suggested in the available guidance. Fortunately, 20 additional trials [ 17 , 44 , 45 ] aiming to investigate the efficacy of tirzepatide in the clinical setting of T2DM or obesity are ongoing. We can obtain more data to analyze after these trials are completed in the near future.…”
Section: Discussionmentioning
confidence: 99%